PBG 11.Genetic diversity and heterotic grouping among selected Philippine corn inbred lines using Llne x tester approach Rica (The Philippine Journal of Crop Science, 2018)
Heterotic grouping was conducted using 12 unknown inbred lines and four identified testers in line x tester approach. All traits showed significant differences.EWL1 had highest significant positive GCA estimates for yield while four crosses(L5 x T2,L7 x T3,L11 x T4 and L12 x T4) had significant positive SCA estimates, L11 xT4 had highest heterosis. Cluster analyses using morpho-agronomic traits, SNP data, and combination of phenotypic and molecular data were performed on parental lines. Based on preliminary assessment, phenotypic evaluation is not reliable. Grouping of lines using SNP data and combination of phenotypic and molecular data showed similar results, since SNP markers used outnumbered the 10 morpho-agronomic traits measured.Waxy corn types (T3 and T4,and L8 to L12) were grouped in one cluster, while sweet corn types and unknown lines (T1 and T2,and L1 to L7) belonged to another cluster. Theoretically, there is a positive correlation between parental divergence and the estimated degree of heterosis, however most parents of crosses with high positive heterosis and SCA estimates for yield were grouped within the same cluster and vice versa. To validate the relationship between genetic distance and heterosis among inbred lines, further testing is recommended.